Antibiotic Stewardship-Twenty Years in the Making - Esmita Charani; Alison Holmes (MDPI AG, 2019)
In the last 20 years, efforts were made to optimize antibiotic use in hospitals across the world as a means of addressing the increasing threat of antibiotic resistance. Despite robust evidence supporting optimal practice, antibiotic decision-making remains sub-optimal in many settings, including in hospitals. Globally, resources remain a limiting factor in the implementation of antibiotic stewardship programs. In addition, antibiotic decision-making is a social process dependent on cultural and contextual factors. Cultural boundaries in healthcare and across specialties still limit the involvement of allied healthcare professionals in stewardship interventions. There is variation in the social norms and antibiotic-prescribing behaviors between specialties in hospitals. The cultural differences between specialties and healthcare professionals (1) shape the shared knowledge within and across specialties in the patient pathway, and (2) result in variation in care, thus impacting patient outcomes. Bespoke stewardship interventions that account for contextual variation in practice are necessary.